2005
DOI: 10.1080/15602210500282434
|View full text |Cite
|
Sign up to set email alerts
|

Use of a learning portfolio for continuous professional development: A study of pharmacists in Ontario (Canada)

Abstract: The use of learning portfolios in health professions has been widely described and discussed as an important tool for promoting reflective practice and continuing professional development. Within pharmacy, there have been reports of the use of the learning portfolio in practice and education. The Ontario College of Pharmacists, as part of its maintenance of competency requirements, requires practicing pharmacists to maintain a learning portfolio as a written record of learning activities, resources used and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 11 publications
1
55
0
3
Order By: Relevance
“…28,35,36,39,40 Of these, two were conducted using the same cohort of pharmacists in Ontario, Canada. 28,35 The Canadian studies identified a variation in the number of reported changes to practice. These changes were based on a self-report questionnaire, a data-collection method that has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28,35,36,39,40 Of these, two were conducted using the same cohort of pharmacists in Ontario, Canada. 28,35 The Canadian studies identified a variation in the number of reported changes to practice. These changes were based on a self-report questionnaire, a data-collection method that has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Austin et al 28 of 1360 pharmacists in Ontario, Canada, the findings suggested that the portfolio had limited effect in promoting self-reflection. The notion of reflection in all the studies reviewed was used in many different ways, making comparisons difficult.…”
Section: Lack Of Benefit To Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Les auteurs ont rapporté que ce processus a fourni une impulsion favorable à l'apprentissage, avec des contraintes de temps adé-quates pour les médecins généralistes. Une enquête menée par Austin et al [24] chez 1415 pharmaciens canadiens soulignait la valeur d'une session de partage d'information, permettant aux participants de discuter des expériences avec des collègues dans un contexte facilitant, et rapportait qu'après cette séance, les individus concernés indiquaient qu'ils étaient «beaucoup plus informés, avertis et favorables à la notion de portfolio ». Dans la petite étude de Tiwari et Tang [15] , chez des étudiants en soins infirmiers, les utilisateurs de portfolios développaient spontanément des stratégies collaboratives d'apprentissage et se soutenaient mutuellement, ceci étant considéré en soi comme un résultat tangible de la participation au processus du portfolio.…”
Section: Le Soutien Des Pairsunclassified